POLITIK GENDER DI RANAH MINANG: Institusi, Gagasan dan Kepentingan - Muhammad Syukri Syukri (Turast: Jurnal Penelitian dan Pengabdian, 2013)
This article is aimed at investigating government’s effort to mainstream gender in all their policy and programusing political economy approach. Despite the fact that Indonesian government has issued several regulationand established organizational support for gender mainstreaming, it is nevertheless not well-functioning atlocal level. Various local contexts have contributed to this ineffective policy. The idea that local tradition hasput women on the top of noble position has become an excuse to not seriously pushing mainstreaming agendaby local key decision maker. At organizational level, lack of knowledge and incentive to implement gendermainstreaming either in policy or program, are the reasons why government institutions do not buy-in theidea at practical level.